Role of positive psychological behaviors, transformational leadership and psychological empowerment in reducing employees` negativity - Mehdi Yazdan Shenas; Amir Hossein Mazidabadi Farahani (پژوهش‌های روانشناختی در مدیریت, 2015)
This study tries to investigate the effects of positive organizational behavior in reducing employees` negativity. In this regard, different relationships between positive psychological capital and transformational leadership with organizational cynicism and employees` intention to quit have been analyzed within the conceptual framework. An important idea is that the psychological empowerment as a mediating factor can affect these relationships which should be carefully considered. This research is a descriptive one which its statistical population consists of employees of Social Security Organization in Qom province and required data were collected through questionnaire. Results show the positive role of psychological capital and transformational leadership in reducing organizational cynicism and intention to quit. Also, analyses supported the mediating role of psychological capital in relations among psychological capital, organizational cynicism, and intention to quit, but this role was not confirmed in relations among transformational leadership, organizational cynicism, and intention to quit.